Illocution and Speaker Intent in Coptic: the Case of the ‘Autofocal’ Second Tenses - Uljas, Sami (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
It is suggested that the so-called ‘autofocal’ second tenses attested in Coptic are characterised by uniform illocutionary properties. In most and perhaps all cases these constructions seem to appear when speakers view the propositional content of what is said as unacceptable, invalid, or, less often, defective in terms of its information value. It is shown that cross-linguistic parallels to these uses are readily forthcoming from other languages, where propositions of similar sort are regularly coded with subjunctive and corresponding forms.